(untitled) (Medical Forum Monthly, 2024)
Objective: To find out the relationship between the training and development on employee performance in hospitals. Study Design: Descriptive and quantitative, cross sectional study. Place and Duration of Study: This study was carried out at National Institute of Business Administration and in private and public hospitals, Lahore from 5th February 2013 to 1st August 2013. Materials and Methods: The independent variables are training and development and employee performance is dependent variable Hypothesis are proposed. Non-probability and simple convenience sampling used for research purpose. Data was collected from the respondents through questionnaires. About 100 Questionnaires were distributed and collected. Results: The study states that there is a positive correlation between training and employee performance. The value of R² is 0.407 which means that 40.7 % variation in the employee’s performance is brought by training and development programs. The value of B₀ is 1.85 which interprets that if there is no investment in training then employee performance will be 1.85. The value of B1 is 0.407 which means that if there is 1 % change in training there will be 40.7 % change in employee performance. Conclusion: The subjected study is directly related to the role of training in increasing the performance of employees and it is found that training plays an effective role in enhancing the capabilities of both new and current employees.